Analisis Kelayakan Finansial Usaha Coffee Defect Robusta di CV Kopi Citarasa Persada - Erson, Davina Azalia; Indah, Pawana Nur; Atasa, Dita (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
CV Kopi Citarasa Persada is on of the coffee agro-industries that processes damaged or defective coffee beans into coffee powder. Coffee defect is famous for its low quality, which makes it a new challenge in the coffee industry. Even so, CV Kopi Citarasa Persada continues to process coffee defects while maintaining the quality of taste that can be well received by its consumers. The purpose of this study is to determine the estimated costs, revenue, and income, as well as to determine the financial feasibility of CV Kopi Citarasa Persada on their coffee defect robusta products. The sample was purposively selected from eight informants who were selected based on certain criteria and in accordance with the research objectives. The result of the research that have been carried out in one production process are the total costs incurred for coffee defect robusta amounting to IDR 851.833, with total revenue of IDR 1.000.000, and revenue generated of IDR 148.167. Obtained a BEP production value of 34 pcs and a BEP price of IDR 21.296, the value of the R/C ratio is 1,17 and the value of the B/C ratio is 0,17. So it cann be concluded that the coffee defect robusta business at CV Kopi Citarasa Persada is feasible in terms of revenue, but not feasible in terms of income.